2005
DOI: 10.1105/tpc.105.030775
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Plant Cysteine Protease Has a Dual Function as a Regulator of 1-Aminocyclopropane-1-Carboxylic Acid Synthase Gene Expression

Abstract: The hormone ethylene influences plant growth, development, and some defense responses. The fungal elicitor Ethylene-Inducing Xylanase (EIX) elicits ethylene biosynthesis in tomato (Lycopersicon esculentum) and tobacco (Nicotiana tabacum) leaves by induction of 1-aminocyclopropane-1-caboxylic acid synthase (Acs) gene expression. A minimal promoter element in the LeAcs2 gene required for EIX responsiveness was defined by deletion analysis in transgenic tomato plants. The sequence between −715 and −675 of the tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 79 publications
(105 reference statements)
1
79
0
1
Order By: Relevance
“…Accumulated evidence shows that the expression of ACS and ACO is induced by various factors, including indole-3-acetic acid, physical injury, cytokinins, ABA, brassinosteroid, ethylene, and other forms of stress (Tsuchisaka and Theologis, 2004;Wang et al, 2005;Hansen et al, 2009). A growing number of studies have reported that multiple regulations are involved in the expression of ACS and ACO (Matarasso et al, 2005;Ito et al, 2008;Lin et al, 2008). For example, tomato LeCp is a dual-function protein that acts as a Cys protease in the cytoplasm and can be SUMO modified to enter the nucleus to directly activate the expression of tomato LeACS2 following attack by a pathogen (Matarasso et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulated evidence shows that the expression of ACS and ACO is induced by various factors, including indole-3-acetic acid, physical injury, cytokinins, ABA, brassinosteroid, ethylene, and other forms of stress (Tsuchisaka and Theologis, 2004;Wang et al, 2005;Hansen et al, 2009). A growing number of studies have reported that multiple regulations are involved in the expression of ACS and ACO (Matarasso et al, 2005;Ito et al, 2008;Lin et al, 2008). For example, tomato LeCp is a dual-function protein that acts as a Cys protease in the cytoplasm and can be SUMO modified to enter the nucleus to directly activate the expression of tomato LeACS2 following attack by a pathogen (Matarasso et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have reported that multiple regulations are involved in the expression of ACS and ACO (Matarasso et al, 2005;Ito et al, 2008;Lin et al, 2008). For example, tomato LeCp is a dual-function protein that acts as a Cys protease in the cytoplasm and can be SUMO modified to enter the nucleus to directly activate the expression of tomato LeACS2 following attack by a pathogen (Matarasso et al, 2005). The MADS box transcription factor RIN plays an important role in regulating the expression of Figure 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, PA dependent inhibition of CTR1 could function synergistically with ethylene and work to promote rapid and/ or heightened activation of ethylene responses. This mechanism could act in parallel with other recently described stress-activated pathways that induce ethylene production through induction of ACC synthase (ACS) gene expression 16 and ACS activity. 12 An advantage of the PA pathway would be its speed.…”
Section: A Model For the Role Of Stress-induced Pa In Inducing Ethylementioning
confidence: 73%
“…5, D-F). As described for other diverse tissues and fruits (Soda et al, 1986;Alonso and Cranell, 1995;Itai et al, 2000;Matarasso et al, 2005), Cys proteases of the secretory pathway are required during ripening and senescence for the degradation and recycling of proteins (Solomon et al, 1999;Matarasso et al, 2005;Ondzighi et al, 2008). Fruit bromelain contains a strong signal peptide (http://www.uniprot.…”
Section: Discussionmentioning
confidence: 95%